2001
DOI: 10.1002/ijc.1294
|View full text |Cite
|
Sign up to set email alerts
|

Family history of cancer and risk of esophageal and gastric cancers in the United States

Abstract: The worldwide rates for histology-and subsite-specific types of esophageal and gastric cancer reveal strikingly divergent patterns. The contribution of environmental and genetic factors has been explored in several high-incidence areas, but data on genetic influences are scarce for Western countries. Using data from a multicenter, population-based, case-control study on 1,143 cases and 695 controls in the United States, we evaluated whether a family history of digestive or other cancers was associated with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
97
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 31 publications
12
97
4
Order By: Relevance
“…H. pylori infection is an established cause of gastric lymphomas of mucosa-associated lymphoid tissue (Wotherspoon et al, 1991;Parsonnet et al, 1994), but we had no details of the non-Hodgkin's lymphoma subtypes. The association of corpus cancer with breast cancer was in line with a US case -control study (Dhillon et al, 2001). Second corpus cancer has been observed to be in excess after primary sporadic and familial breast cancers (Ji and Hemminki, 2006); BRCA1, BRCA2, and E-cadherin gene may be shared genetic risk factors for the two cancer sites.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…H. pylori infection is an established cause of gastric lymphomas of mucosa-associated lymphoid tissue (Wotherspoon et al, 1991;Parsonnet et al, 1994), but we had no details of the non-Hodgkin's lymphoma subtypes. The association of corpus cancer with breast cancer was in line with a US case -control study (Dhillon et al, 2001). Second corpus cancer has been observed to be in excess after primary sporadic and familial breast cancers (Ji and Hemminki, 2006); BRCA1, BRCA2, and E-cadherin gene may be shared genetic risk factors for the two cancer sites.…”
Section: Discussionsupporting
confidence: 77%
“…However, according to the authors, the result could be overestimated by reporting bias (Lagergren et al, 2000). A nonsignificant excess of cardia cancer was also noted in an US study among individuals reporting a family history of digestive tract cancers (Dhillon et al, 2001). In the present study, we observed a strong familial association between oesophageal adenocarcinoma and cardia cancer, giving an SIR of 5.67.…”
Section: Discussionsupporting
confidence: 74%
“…Two previous case-control studies have reported that family history of esophageal cancer is associated with the risk of breast cancer [10,13], and one of the studies found that the risk was mainly seen in early onset breast cancers, which is consistent with our finding [10]. Although, no studies have reported that family history of lung cancer is associated with early onset breast cancer, two case-control studies found that non-smoking lung cancer was associated with a family history of breast cancer [25,39].…”
Section: Discussionmentioning
confidence: 99%
“…What's more, genetic factor may also be one of main factors influencing gastric cardia cancer in this study. The correlation between the cardia gastric cancer and family history of tumor suggested that genetic predisposition and common dietary habits might contribute to the cardia carcinogenesis (Dhillon et al, 2001;Wen et al, 2010). The migration epidemiology had demonstrated that the incidences for esophageal cancer in the offspring of immigrants who migrated to Shanxi province 108 years ago were the same as native counterparts in Linzhou (Wang et al, 2005).…”
Section: Control Study On Risk Factors For Gastric Cardia Cancer In Rmentioning
confidence: 99%